Epidemiological Trends and Attributable Risk Burden of Cervical Cancer: An Observational Study from 1990 to 2019 - Hu Yao; Chen Yan; He Qiumin; Zhou Li; Ai Jiao; Li Xin; Li Hong (International Journal of Clinical Practice)
Background. Cervical cancer, especially in underdeveloped areas, poses a great threat to human health. In view of this, we stratified the age and social demographic index (SDI) based on the epidemiological development trend and attributable risk of cervical cancer in countries and regions around the world. Methods. According to the data statistics of the global burden of disease database (GBD) in the past 30 years, we adopted the annual percentage change (EAPCs) to evaluate the incidence trend of cervical cancer, that is, incidence rate, mortality, and disability adjusted life expectancy (DALY). Meanwhile, we investigated the potential influence of SDI on cervical cancer’s epidemiological trends and relevant risk factors for cervical cancer-related mortality. Results. In terms of incidence rate and mortality, the high SDI areas were significantly lower than those of low SDI areas. The incidence and mortality in women aged 20 to 39 were relatively stable, whereas an upward trend existed in patients aged 40 to 59. The global cervical cancer incidence rate increased from 335642 in 1990 to 565541 in 2019 (an increase of 68.50%, with an average annual growth rate of 2.28%), while the age-standardized incidence rate (ASIR) showed a slight downward trend of 14.91/100000 people (95% uncertainty interval [UI], 13.37-17.55) in 1990 to 13.35/100,000 persons (95% UI, 11.37-15.03) in 2019. The number of annual deaths at a global level increased constantly and there were 184,527 (95% UI, 164,836-218,942) deaths in 1990 and 280,479 (95% UI, 238,864-313,930) deaths in 2019, with an increase of 52.00%(average annual growth rate: 1.73%). The annual age-standardized disability adjusted annual life rate showed a downward trend (decline range: 0.95%, 95% confidence interval [CI], from −1.00% to − 0.89%). In addition, smoking and unsafe sex were the main attributable hazard factors in most GBD regions. Conclusions. In the past three decades, the increase in the global burden of cervical cancer is mainly concentrated in underdeveloped regions (concentrated in low SDI). On the contrary, in countries with high sustainable development index, the burden of cervical cancer tends to be reduced. Alarmingly, ASIR in areas with low SDI is on the rise, which suggests that policy makers should pay attention to the allocation of public health resources and focus on the prevention and treatment of cervical cancer in underdeveloped areas, so as to reduce its incidence rate, mortality, and prognosis.